New Clinical Aspects of Eplerenone Use in Clinical Practice - S. R. Gilyarevskiy; N. G. Bendeliani; M. V. Golshmid; I. M. Kuzmina (Столичная издательская компания, 2018)
The problem of the discrepancy between convincing evidences of the effectiveness of the use of mineralocorticoid receptor antagonists in patients with heart failure with reduced left ventricular ejection fraction and insufficiently frequent their use in clinical practice for the treatment of these patients is considered in the article. Experts opinions on the reasons for this discrepancy are also presented. New data on the effectiveness of the use of the mineralocorticoid receptor antagonist, eplerenone, in some clinical situations identified in the analysis of subgroups of participants in a large randomized clinical trial EMPHASIS-HF are discussed. The main goal of this study was to evaluate the efficacy of eplerenone compared with placebo in patients with heart failure and reduced left ventricular function. In addition, experimental animal studies, which may indicate the pleiotropic effects of eplerenone in patients with vascular diseases, are presented. The new data on the effectiveness of eplerenone in subgroups of patients with heart failure and certain characteristics may be an additional reason to draw the attention of physicians to the benefits of its use and, accordingly, its more frequent application in clinical practice for the treatment of patients with clear indications for this therapy.